EFEKTIVITAS PEMBERIAN KAPSUL IODIUM DOSIS TINGGI TERHADAP STATUS IODIUM WANITA USIA SUBUR (WUS) YANG MENGKONSUMSI BAHAN MAKANAN SUMBER SIANIDA TINGGI - M. Saidin; Sukati S.; Suryati K.; Dhoni Kristanto; Samsudin Samsudin (Persagi, 2004)
THE EFFECTIVENESS OF ORAL HIGH DOSE IODINE SUPPLEMENTATION TO IODINE STATUS OF CHILDBEARING AGE WOMEN CONSUMING OF FOOD HIGH IN CYANIDE CONTENT.Background: It was reported by Iodine Deficiency Disorder Research Institute of Ministry of Health that prevalence of childbearing age women (CBAW) with abnormal of serum Thyroid Stimulating Hormone (TSH) value in Magelang district was around 23%, while Urine Iodine Excretion (UIE) considered normal (112 πg/L). The average of cyanide content of daily food consumed was 29.4 mg/day. These findings indicated that there was a relationship between cyanide consumed and Iodine Deficiency Disorder (IDD). As one of goitrogenic agents, cyanide inhibited Iodide (I) entering into thyroid cells, further more disturbed process of thyroid hormone (T4 and TSH) synthesis. Objectives: To investigate the effect of the supplementation of high dose Iodine by oral (capsules) to iodine status of childbearing age women consuming foods high cyanide in IDD endemic area. Methods: The study design was